(Super)hydrophobic coating of orthodontic dental devices and reduction of early oral biofilm retention. (3rd November 2015) - Oliveira, Adauê S; Kaizer, Marina R; Azevedo, Marina S; Ogliari, Fabrício A; Cenci, Maximiliano S; Moraes, Rafael R
Abstract: This study was designed to apply (super)hydrophobic crosslinked coatings by means of a sol-gel process on the surface of orthodontic devices and investigate the potential effect of these coatings in reducing the early retention of oral biofilm. Two organosilane-based hydrophobic solutions (HSs) were prepared containing hexadecyltrimethoxysilane diluted in ethanol (HS1) or 1H, 1H, 2H, 2H -perfluorodecyltriethoxysilane diluted in dimethyl sulfoxide (HS2). Stainless steel plates and ceramic discs were coated with HS1 or HS2 and heated at 150 °C for 2 h for condensation of a crosslinked SiO x network. Organosilane coatings were applied after previous, or no, surface sandblasting. Commercial stainless steel and ceramic brackets were used to evaluate oral biofilm retention after 12 h or 24 h of biofilm growth, using a microcosm model with human saliva as the inoculum. Surface roughness analysis (Ra, μ m) indicated that sandblasting associated with organosilane coatings increased roughness for stainless steel brackets only. Analysis of the water contact angle showed that the stainless steel surface treated with HS1 was hydrophobic (~123°), while the ceramic surface treated with HS2 was superhydrophobic (~155°). Biofilm retention after 24 h was significantly lower in groups treated with hydrophobic coatings. An exponential reduction in biofilm accumulation was associated with increased water contact angle for both stainless steel and ceramic at 24 h. Application of (super)hydrophobic coatings on the surface of stainless steel and ceramic orthodontic devices might reduce the retention of oral biofilm.